Fighting, Loving, Teaching Exploration of Hope, Armed Love and Critical Urban Pedagogies - Daniels, Emily A.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Despite challenges and continuing inequalities surrounding urban education, there are instances which provide a counter narrative to the dominant discourses of failure. Urban educators who engage conscious caring and (3z(Barmed love(3y (Bin their practice are an example of this. This qualitative instrumental case study examines the practices of two transformative urban educators, around caring and armed love in their classroom praxis. This study examines their conceptions and practice of these approaches through interview, field-notes and video data. The findings involve manifestations of both caring and armed love, including connection, nurturance through food, community, directness, relationships, honesty, respect and demand, as well as high expectations. Despite the challenges that surrounded this school, the atmosphere of caring and armed love acted like a protective barrier or space of safety for the students. My conclusion points to the vital significance of re-humanizing our educational discourse in favor of the genuine care and connections that exist in urban settings, and the importance of re-centering our discussion to focus on the human aspects of education which lie at the core of our profession. Firmly anchored in a critical educational tradition of struggle, Fighting, Loving, Teaching reawakens teachers to educational justice and the everyday possibilities of a pedagogy of the heart. With uncompromising passion and commitment, this timely book weaves a narrative of critical persistence and radical hope, in an effort to reinsert the revolutionary power of love into current discourses of democratic schooling and society. Antonia Darder Leavey Endowed Chair of Ethics and Moral Leadership Loyola Marymount University, Los Angeles Author of Reinventing Paulo Freire: A Pedagogy of Loves
Keywords: Education; Education; Education (general).